2009
DOI: 10.1590/s1517-83822009000200013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of siderophore-producing bacteria of tobacco rhizosphere

Abstract: The genetic diversity of siderophore-producing bacteria of tobacco rhizosphere was studied by amplified ribosomal DNA restriction analysis (ARDRA), 16S rRNA sequence homology and phylogenetics analysis methods. Studies demonstrated that 85% of the total 354 isolates produced siderophores in iron limited liquid medium. A total of 28 ARDRA patterns were identified among the 299 siderophore-producing bacterial isolates. The 28 ARDRA patterns represented bacteria of 14 different genera belonging to six bacterial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 12 publications
3
52
0
2
Order By: Relevance
“…Different PGPR strains have a stimulative effect on the growth and development of plants by means of synthesis of phytohormones (Vessey 2003), siderophore production (Tian et al 2009), transformation of inaccesible P forms into forms accesible to plants (Chen et al 2006) and other ways. To what extent this stimulative effect will affect the plant yield depends on the type of soil, effectivenes of the indigenous and introduced strains of microorganisms, plant species, agrotechnical measures etc.…”
Section: Resultsmentioning
confidence: 99%
“…Different PGPR strains have a stimulative effect on the growth and development of plants by means of synthesis of phytohormones (Vessey 2003), siderophore production (Tian et al 2009), transformation of inaccesible P forms into forms accesible to plants (Chen et al 2006) and other ways. To what extent this stimulative effect will affect the plant yield depends on the type of soil, effectivenes of the indigenous and introduced strains of microorganisms, plant species, agrotechnical measures etc.…”
Section: Resultsmentioning
confidence: 99%
“…Siderophore secretion by some strains of Achromobacter xylosoxidans isolated from soil has been reported (Tian et al, 2009); however, no investigations of clinical isolates have been reported. There are no reports of siderophore production by H. influenzae; however, comparative genomics has identified an operon for ferrichrome utilization in non-typable H. influenzae strains (Morton et al, 2010).…”
Section: Siderophore-mediated Iron Acquisitionmentioning
confidence: 99%
“…Many reports reveal the ability of both gram negative bacterial isolates (Pseudomonas sp.) and bacterial genera of Bacillus and Rhodococcus that belongs to the gram positive group with the capability to produce siderophores [34]. In this study siderophore production was observed in Enterobacter aerogenes A23.…”
Section: Discussionmentioning
confidence: 61%